Absorptive Properties of PA6 as Drug Delivery Container. (2016) - Aulova, Alexandra; Emri, Igor
Abstract: In order to check absorptive properties of PA6 and its ability to store molecules of different size and polarity, the absorption tests were performed. Since it is well known that PA6 absorbs water molecules, it was decided to test distilled water solutions of different substances with different particle size and polarity. Distilled water was taken as reference. Solutions of glucose with neutral large molecules and salt with small ions of calcium and chloride were prepared. Gravimetrically casted PA6 specimens were submerged into the solutions for 33 days, while their mass gain was measured. Presence of the molecules inside of the material was checked by Energy dispersive X-ray (EDS) and Proton Nuclear Magnetic Resonance (NMR) methods. Results showed that chlorine and sodium ions, as well as glucose molecules penetrated into the material. This means that it absorbs molecules of various polarity and size and can be considered as drug delivery container.